Clinical Study of Nasopharyngeal Carcinoma Treated by Helical Tomotherapy in China: 5-Year Outcomes. (9th July 2014) - Du, Lei; Zhang, Xin-Xin; Ma, Lin; Feng, Lin-Chun; Li, Fang; Zhou, Gui-Xia; Qu, Bao-Lin; Xu, Shou-Ping; Xie, Chuan-Bin; Yang, Jack
Abstract : Background. To evaluate the outcomes of nasopharyngeal carcinoma (NPC) patients treated with helical tomotherapy (HT). Methods. Between September 2007 and August 2012, 190 newly diagnosed NPC patients were treated with HT. Thirty-one patients were treated with radiation therapy as single modality, 129 with additional cisplatin-based chemotherapy with or without anti-EGFR monoclonal antibody therapy, and 30 with concurrent anti-EGFR monoclonal antibody therapy. Results. Acute radiation related side effects were mainly grade 1 or 2. Grade 3 and greater toxicities were rarely noted. The median followup was 32 (3–38) months. The local relapse-free survival (LRFS), nodal relapse-free survival (NRFS), distant metastasis-free survival (DMFS), and overall survival (OS) were 96.1%, 98.2%, 92.0%, and 86.3%, respectively, at 3 years. Cox multivariate regression analysis showed that age and T stage were independent predictors for 3-year OS. Conclusions. Helical tomotherapy for NPC patients achieved excellent 3-year locoregional control, distant metastasis-free survival, and overall survival, with relatively minor acute and late toxicities. Age and T stage were the main prognosis factors.